Between You and Me: Transitional Comics - Councilor, K. C. (Drawbridge Press, 2019)
"Between You and Me: Transitional Comics is a collection of comics that reflects two transitions–from a person who doesn't draw to a cartoonist and from a butch lesbian to a transgender dude. I stopped drawing when I was a kid and didn't start drawing again until I was 33 years old and brave enough to take a course with Lynda Barry at the University of Wisconsin-Madison. In the four years since, I have continued working closely with her, and in that time, I have quite literally drawn myself into being. It was through the experience of drawing myself in the world on the page that allowed me to draw myself out into the world, to realize that I am transgender and that I wanted to transition–something I had been thinking about for nearly a decade but kept private and suppressed. The comics in Between You and Me reflect the experiences of a transgender and transitioning person navigating the profundities and mundanities of daily life and observing the world around him. Also present in the book is my transition from non-drawer to someone who identifies as a cartoonist. Though not linearly, readers will note a shift in the confidence of the line as my fluency as an artist increased. The book includes a back section that includes a letter to the reader, early sketchbook pages and commentary on being self-conscious, encouraging people to reclaim drawing as a form of self-expression and a way of looking at the world. The book concludes with a dialogue between me and Lynda Barry, a conversation between student and teacher about gender and drawing and discovery and identity and growing up and everything in between (and then some)! The book includes reflections that expand beyond my own life and experiences to address social issues. This comes from my grappling with the sincere belief that it is possible for people to fundamentally change–I don't think people actually want to be "haters"–while at the same time witnessing the violences of racist oppression, patriarchy, and homophobia. The book is entirely nonfiction, but it's not wholly a memoir, and certainly doesn't aim to represent any kind of authoritative version of trans experience. The specifics of my experiences of walking down the street, going to the bathroom, going through airport security or to the doctor, of coming out and not coming out are at once particular to my experience and resonate with the sticking points where many trans and gender-fluid people experience confusion, frustration, fear, and delight"–Author's website.
Keywords: Biography; Biography; Comic books; strips; etc; Biography; Female-to-male transsexuals; Biography; Female-to-male transsexuals; Female-to-male transsexuals; Cartoonists; Comic books; strips; etc; Comic books; strips; etc; Cartoonists; Comic books; strips; etc; Female-to-male transsexuals; United States; Medicine; dept.com; faculty_collection